ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP LOAN TO FUNDING RATIO PADA BANK KOMERSIL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011 - 2016 - Suci Zulkifli; Muhammad Ali; Andi Aswan (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
The capital market is one of the long-term alternative funding options for companies, including companies in the banking sector.This study aims to identify and analyze the influence of Cap (Capital Adequacy Ratio (CAR), Non Performing Loan (NPL) and Operational Costs to Operating Income (BOPO) affecting Loan To Funding Ratio (LFR) as well as to know and analyze the factors that most influence on Loan To Funding Ratio (LFR) at Commercial Banks listed on the Indonesia Stock Exchange. The type of research used in this study is quantitative approach. The quantitative approach bases the study of empirical rational principles. The quantitative approach bases the study of empirical rational principles. Therefore, before doing the research the researcher must find the problem and hypothesis to be tested based on the criteria specified and the analytical tool used multiple linear regression to know the relation of Capital Adequacy Ratio, Non Performing Loan (NPL), Operating Cost to Operational Revenue (BOPO) on financial performance is measured using the Loan to Funding Ratio (LFR) ratio. The result of the research shows that Capital Adequacy Ratio (CAR) has significant influence to Loan to Funding Ratio (LFR), Non Performing Loan (NPL) has significant effect to Loan to Funding Ratio (LFR), BOPO has no significant effect on Loan to Funding Ratio (LFR) at Commercial Commercial Banks listed on the Indonesia Stock Exchange. While Capital Adequacy Ratio, Non performing Loan and BOPO there is a simultaneous or simultaneous relationship to Loan to Funding Ratio (LFR) at Commercial Bank Commercial listed in Indonesia Stock Exchange Keywords: Non performing Loan, BOPO, Loan to Funding Ratio